2008
DOI: 10.1177/0040517507083547
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Modeling the Dynamic Drape of Four Natural-fiber Fabrics

Abstract: This study primarily analyzed the dynamic drape coefficient of four natural-fiber fabrics at speeds of 0—450 rpm. A tangent partition method was used to divide the drape coefficient curve into four regions, characterized as drape coefficient increment initial growth, fast growth, slow growth and dynamic stable regions. The ANOVA test was used for validation. The dynamic drape coefficients of these four natural-fiber fabrics were then compared. The order of the drape coefficient of these fabrics changed three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Lin et al [58]studied the dynamic drapeability of four natural fabrics at a wider range of revolution speeds (0 -450)rpm for a sample disc with 18 cm diameter. Images were captured for fabrics tested at 25 rpm regular intervals.…”
Section: Commented [U50]mentioning
confidence: 99%
“…Lin et al [58]studied the dynamic drapeability of four natural fabrics at a wider range of revolution speeds (0 -450)rpm for a sample disc with 18 cm diameter. Images were captured for fabrics tested at 25 rpm regular intervals.…”
Section: Commented [U50]mentioning
confidence: 99%
“…Plots of experimental drape coefficients showed that the order of the fabrics was dependant on the revolution speed at which the DC was measured. Their order was changed three times in the fast growth stage and returned to the initial growth order and became stable at the two periods following the fast growth (slow growth and dynamic stable) [23].…”
Section: Dynamic Drapemetermentioning
confidence: 99%
“…Lin et.al. analyzed the dynamic drape coefficient of four natural-fiber fabrics at speeds of 0-450 rpm [13]. A linear model, a growth model and a nonlinear logistic model were used to analyze the dynamic drape coefficient curve fit, and the F-test was used for validation.…”
Section: Introductionmentioning
confidence: 99%